Endoscopic harvesting of the greater saphenous vein for aortocoronary bypass grafting. - Carrizo, G J (1999)
We conducted an observational study to evaluate the effectiveness of an endoscopic technique for harvesting the greater saphenous vein for aortocoronary bypass grafting. We hypothesized that the endoscopic technique would minimize the risk of postoperative wound complications. From May 1997 to July 1998, we used an endoscopic technique to harvest the greater saphenous vein in 50 patients who underwent aortocoronary artery bypass grafting. Twenty-five of the patients had an increased risk for wound complications due to preexisting diabetes, obesity, peripheral vascular disease, or lymphedema. The average duration of the procedure was 39 minutes (range, 11 to 70 minutes). The average length of the harvested vein was 58 cm (range, 25 to 85 cm). We made an average of 2.5 incisions per patient (range, 1 to 5 incisions), and the average incision length was 7 cm (range, 3 to 10 cm). Two patients (4%) required conversion to an open technique using 5 small incisions. Postoperative complications included 1 wound infection (2%) and 1 small hematoma (2%). Two patients (4%) had minor erythema at the incision site, and 5 patients (10%) had postoperative lymphedema. The most common problem, ecchymosis, was seen in 6 patients (12%). None required repeat hospitalization or reoperation for wound complications. In our study, the endoscopic approach yielded superior cosmetic results, and reduced wound complications and discomfort, compared with traditional methods of vein harvesting. After gaining expertise with this minimally invasive method of vein harvesting, a surgeon can safely remove the saphenous vein in 20 to 30 minutes.